2022
DOI: 10.3389/fmed.2022.931379
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of the multidrug-resistant Chryseobacterium indologenes isolated from a patient in Brazil

Abstract: Chryseobacterium indologenes is a non-glucose-fermenting Gram-negative bacillus. This emerging multidrug resistant opportunistic nosocomial pathogen can cause severe infections in neonates and immunocompromised patients. This study aimed to present the first detailed draft genome sequence of a multidrug-resistant C. indologenes strain isolated from the cerebrospinal fluid of an infant hospitalized at the Neonatal Intensive Care Unit of Brazilian Tertiary Hospital. We first analyzed the susceptibility of C. ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 171 publications
0
13
0
Order By: Relevance
“…Babies are more vulnerable to colonization and infection with pathogens due to an immature immune system. Novel molecular and phenotypic methods are providing more accurate and robust identification of these pathogens ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Babies are more vulnerable to colonization and infection with pathogens due to an immature immune system. Novel molecular and phenotypic methods are providing more accurate and robust identification of these pathogens ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The penP gene encodes a narrow-spectrum β-lactamase that displays a more effective hydrolysis only of first—and second—generation penicillins and cephalosporins ( 44 46 ). The bla TEM-116 gene has been reported in a variety of clinical isolates ( 28 , 47 ). Studies have related that TEM-116 β-lactamase can confer resistance to ceftazidime, cefotaxime, and aztreonam ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genus Chryseobacterium is composed of more than 130 species [ 50 ], the majority of information about Chryseobacterium antibiotic resistance has been obtained from three main human-infecting species: C. indologenes , C. meningosepticum , and C. gleum [ 51 ]. Clinical Chryseobacterium isolates are known to be highly resistant to most β-lactam agents, aminoglycosides, tetracyclines, macrolides, chloramphenicol, erythromycin, and ticarcillin-clavulanate [ 11 , 26 , 52 , 53 ]. Information about the resistance of the environmental Chryseobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, no specific Chryseobacterium proteins responsible for tetracycline resistance have been confirmed yet. Chryseobacterium resistance to aminoglycosides is also well documented [ 11 ]; efflux pumps and antibiotic-modifying enzymes have been shown to be coded in sequenced Chryseobacterium genomes [ 53 , 60 ]. In this study, we found Chryseobacterium streptomycin resistance gene ant(6) , which is widespread in genus Chryseobacterium .…”
Section: Discussionmentioning
confidence: 99%